2022
DOI: 10.1021/acs.langmuir.2c00206
|View full text |Cite
|
Sign up to set email alerts
|

Urea Disrupts the AOT Reverse Micelle Structure at Low Temperatures

Abstract: Aside from its prominent role in the excretory system, urea is also a known protein denaturant. Here, we characterize urea as it behaves in confined spaces of AOT (sodium bis(2-ethylhexyl) sulfosuccinate) reverse micelles as a model of tight, confined spaces found at the subcellular level. Dynamic light scattering revealed that low temperatures (275 K) caused the smallest of the reverse micelle sizes, w 0 = 10, to destabilize and dramatically increase in apparent hydrodynamic diameter. We attribute this to ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…This tight packing causes a decrease in the aqueous core radius. Others have reported an increase in hydrodynamic radius from DLS studies; 23 this effect is Table 3. Structural Parameters Obtained from SAXS Data by Model-Dependent Fitting a 1-butanol The RM volume fraction, f p , is fixed at 0.32 for CTAB/1-butanol RMs and 0.4 for CTAB/1-hexanol RMs.…”
Section: Langmuirmentioning
confidence: 86%
See 1 more Smart Citation
“…This tight packing causes a decrease in the aqueous core radius. Others have reported an increase in hydrodynamic radius from DLS studies; 23 this effect is Table 3. Structural Parameters Obtained from SAXS Data by Model-Dependent Fitting a 1-butanol The RM volume fraction, f p , is fixed at 0.32 for CTAB/1-butanol RMs and 0.4 for CTAB/1-hexanol RMs.…”
Section: Langmuirmentioning
confidence: 86%
“…They observed that even without significant changes in RM radius and shape, urea enhances the attractive interactions between RM droplets (increasing the attractive potential well depth) and induces percolation. From 2D NOESY studies on AOT/isooctane/water/urea RMs, Miller and Levinger 23 observed that at 2 M concentration, urea is embedded at the RM interface at low water loading ratio (w 0 ). This leads to a drastic increase in RM size and polydispersity on lowering the temperature to 273 K. However, ultrafast pump−probe spectroscopy 26 has highlighted that the hydrogen bonding of water with sulfonate head groups from AOT is significantly more directional compared to bromide counterions from CTAB molecules.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The properties of water shift inside the nanoconfinement, sometimes quite dramatically. For instance, previous results show a size-dependent drop in both rotational and translation water motion, and even the hydrogen exchange with protic solutes in reverse micelles slows down. , There are also unique spectroscopic signatures seen in nanoconfined water from numerous sources, clearly demonstrating that nanoconfinement is a unique environment with behavior not seen in bulk solutions. Several studies have suggested that the solutes inside the nanoconfined water pool are not uniformly distributed but tend to preferentially be observed at the interface. ,, This has led to the general assumption that there are two water populations inside reverse micelles, a core and a shell population, which itself introduces another interesting issue about the behavior of water in nanoconfinement. That is, if the properties of both water and any solutes dissolved within a reverse micelle vary with proximity from the interface, then the shape of the reverse micelle plays a pivotal role in the behavior observed in nanoconfinement.…”
Section: Introductionmentioning
confidence: 99%
“…Isothermal titration calorimetry (ITC) and proton nuclear magnetic resonance ( 1 H NMR) and two-dimensional nuclear Overhauser enhancement spectroscopy (2D NOESY) are powerful techniques used to study the interactions of mixed surfactant systems. ITC is employed to measure the binding thermodynamic of polymer–surfactant complexation, hydrogel formation, polymer aggregation, micellization, and guest–host complexation. Additionally, it can also be used to study the dissociation of micelles into monomers or the formation of micelles with increasing surfactant concentration.…”
Section: Introductionmentioning
confidence: 99%